The Komponen Mu’jam Al Lughah Al Arabiyyah Al Mu’ashiroh ( Studi Analisis Ditinjau dari Ilmu Leksikografi ) - Ryan Nurdiana (Tarling : Journal of Language Education, 2023)
This study aims to describe the components of the Mu'jam Al Lughah Al Arabiyyah Al Mu'ashiroh dictionary. This dictionary is an ekabahasa dictionary that contains the lexical meanings of contemporary Arabic. This research uses a type of descriptive qualitative research with a literature method. This research seeks to elaborate a component analysis of the dictionary written by Ahmad Mukhtar Umar where this dictionary is very popular in egypt and in the arab world in general. Data is collected through careful reading and analyzing through content analysis to find out the components of the dictionary comprehensively. The finding is that this dictionary is quite ideal where its components consist of the initial part, the core part, and the final part which contains enough important information regarding how to use it and contextual examples. Keywords : Dictionary, Mu'jam Al Lughah Al Arabiyyah Al Mu'ashiroh, Lexicography